A study of factors that influence customers satisfaction towards online shopping in Klang Valley / Marina Mohd Kasim - Mohd Kasim, Marina (Faculty of Business and Management, 2015)
The meaning of online shopping is purchasing products or services over the Internet. Online shopping has grown in popularity over the years, mainly because people find it convenient and easy to bargain shop from the comfort of their home or office. One of the most enticing factor about online shopping, particularly during a holiday season, is it alleviates the need to wait in long lines or search from store to store for a particular item. The growth of online shopping is increasing at a rapid rate in Malaysia by replacing traditional store shopping habit of the substantial number of consumers. Based on Chai Fang Tan, 2012, the Internet has opened the door for new approaches to trading and commerce. It is means the internet nowadays give more opportunities to organization or firms. Nowadays people can make some business through internet or online business. According to therakyatpost.com media social, the online shopping in Malaysia increase from 29 million in 2011 to 40 million in 2014. Malaysian is the developing country that increasing involve in online shopping. The growing use of Internet in Malaysia provides a developing prospect for online shopping. The online shopping means the business do not have any concrete or brick building, and they only run their business thru internet. The people will visit their website to see the product that they provide, for example Zalora, Mudah.com and Instagram. There are many factors that can influence consumer’s satisfaction towards online shopping like trust, satisfactions towards the product or the service provided, price and the quality of the products. According to kotler et al. (2009), in Ali Malik et al, (2011) defined as satisfaction as a person feelings of pleasure that result from comparing a product perceived performance (or outcome) to their expectation. It is also means that the products performance meets the consumer’s expectation. The buying process through the online or internet might be the new experiences towards the Malaysian consumers. Online shopping also called internet shopping or electronic shopping, defined as the shopping process where consumers purchase goods or services from any vendors through online (Mastercard Worldwide Insights, 2008). Online shopping in Malaysia can be considered as a new pattern of shopping since it has just began to invade the consumer and retailers in Malaysia. Malaysia can be considered a late starter compared to eight other countries in Asia Pacific that had shown a tremendous online shopping market and create huge revenue to the online business. The online business in Malaysia was growing to the stage that the existence of a lot of online shopping in internet such as Instagram, Facebook and Twitter. Therefore, the main objective is to study the behavior of Malaysian consumers towards online shopping, second to investigate the level of satisfaction of Malaysian consumers towards online shopping and the trust of Malaysian consumers to go online shopping.